Fostering Performance Among Indonesian Ebusiness Start-Ups: The Role Of Innovation Capability With Dynamic Capabilities - Dewi, Yuli Kartika (2024)
The objective of this study is to emphasize the impact of innovation capability on e-business performance by examining the presence of dynamic capabilities and the influence of government support and entrepreneurial orientation within organizations. This research aims to strengthen the correlation between dynamic capabilities and e-business performance. The performance of e-business start-ups is vital for enhancing the stability of a nation's economy, since these enterprises possess the ability to operate flexibly and swiftly adjusting to technological advancements in the digital age. Prior research has extensively examined the significance of innovation and dynamic organizational capacities, establishing them as crucial elements for enhancing a company's performance. However, research pertaining to this problem, particularly in the context of digital firms, has received limited attention, resulting in a scarcity of available materials from prior studies. Information was obtained from 117 e-commerce start-up enterprises that have been active in Indonesia for a period of less than 5 years. The survey was carried out by distributing questions using email and Google Form digital platforms, and subsequently analysed using PLS software version 3.0. The findings are anticipated to address the knowledge gap identified in the literature review and contribute a novel discovery that enhances and supplements the study of RBV theory and dynamic capabilities, particularly in relation to the performance of e-business start-ups in developing nations.